ESPEN practical guideline: Clinical Nutrition in inflammatory bowel disease. Issue 3 (March 2020) - Bischoff, Stephan C.; Escher, Johanna; Hébuterne, Xavier; Kłęk, Stanisław; Krznaric, Zeljko; Schneider, Stéphane; Shamir, Raanan; Stardelova, Kalina; Wierdsma, Nicolette; Wiskin, Anthony E.; Forbes, Alastair
Summary: The present guideline is the first of a new series of "practical guidelines" based on more detailed scientific guidelines produced by ESPEN during the last few years. The guidelines have been shortened and now include flow charts that connect the individual recommendations to logical care pathways and allow rapid navigation through the guideline. The purpose of the present practical guideline is to provide an easy-to-use tool to guide nutritional support and primary nutritional therapy in inflammatory bowel disease (IBD). The guideline is aimed at professionals working in clinical practice, either in hospitals or in outpatient medicine, and treating patients with IBD. In 40 recommendations, general aspects of care in patients with IBD, and specific aspects during active disease and in remission are addressed. All recommendations are equipped with evidence grades, consensus rates, short commentaries and links to cited literature.